Machine learning approach for tenaga nasional berhad (tnb) overhead powerline and electricity pole inventory using mobile laser scanning data - Mohd Rapheal M.S.A.; Farhana A.; Mohd Salleh M.R.; Abd Rahman M.Z.; Majid Z.; Musliman I.A.; Abdullah A.F.; Abd Latif Z. (International Society for Photogrammetry and Remote Sensing, 2023)
Decision trees; Laser applications; Learning algorithms; Machine learning; Mean square error; Scanning; Classifieds; Electricity assets; Electricity pole; Laser scanner data; Laserscanners; Machine-learning; Mobile laser scanner; Overhead powerline; Point-clouds; Power lines; Poles